Coping skills and self-efficacy as predictors of gymnastic performance - Daroglou, G. (The Sport Journal, 2011)
Abstract: The purpose of this study was to examine the way that gymnastic performance can be discriminated based on psychological skills and self-efficacy. The sample of the study was 101 gymnasts (Mage = 11.8 ±.74 years, 22 male and 79 female), who competed at the Hellenic Championship of Rhythmic Gymnastics and the Hellenic Championship of Artistic Gymnastics. Each completed a Self-efficacy scale one day prior to the competition and the Athletic Coping Skill Inventory - 28 immediately following the event. All subscales of the ACSI-28 showed adequate internal consistency (a>.64). A discriminant function analysis suggested that the predictors for distinguishing between poor and high level performance were: Coping with adversity (F=9.3, p<.01); Goal Setting/mental preparation (F=8.58, p<.005); Confidence (F=8.81, p<.005); Freedom from Worry (F=4.83, p<.05); Coachability (F=6.81, p<.01); and Self-efficacy (F=18.9, p<.001). The results indicated that best performance was achieved by those gymnasts who believed they could relax and compete with enthusiasm and certainty, set goals and prepare themselves for the competition, did not worry excessively about their performance, and showed confidence they could perform at a high level. According to the findings of this study, ability alone must not be the only concern of coaches. They also need to enhance certain psychological skills of their gymnasts at an early age, in order for them to have successful outcomes in a competition. More specifically, gymnasts need to learn how to cope with adversity and free themselves from worry, how to use goal setting techniques and prepare themselves for the competition, and how to improve their self-efficacy and confidence.